Development of Healthier meat balls using Walnut Kernels and Fat modifications - Chisti, Hafsa Imtiyaz; Ahmad, Sheikh Rafeh; Sofi, Asif Hassan; Haq, Tarteela; Nazir, Tahir (Journal of Meat Science, 2024)
The current study was aimed at optimizing the amount of fat and walnut kernel content for the production of functional meat balls (locally called as Rista). In the first experiment, different combinations of lean meat, animal fat and vegetable fat (T1 = 90% lean meat: 10% animal fat; T2 = 90% lean meat: 5% animal fat: 5% vegetable fat; T3 = 90% lean meat: 10% vegetable fat) were compared to control (T0 = 80% lean meat: 20% animal fat). Based on physico-chemical, proximate, antioxidant activity parameters and sensory scores, T1 (90% lean meat: 10% animal fat) was found optimum for the formulation of functional meat balls. In the second experiment, walnut kernel paste (WKP) was incorporated at three levels (3, 6 and 9%) replacing lean meat in the formulation of gravy based product. 6% WKP was found optimum for the development of functional meat balls. It was concluded that the formulation containing 84% lean meat, 10% animal fat and 6% walnut kernel paste was suitable for the preparation of functional meat balls.